Stories about the partition of India - Bhalla, Alok (New Delhi : Manohar Publishers, 1994)
Comprehensive selection of stories chiefly from India, Pakistan, and Bangladesh.
Keywords: Short stories, Indic -- Translations into English; Short stories, Urdu -- Pakistan -- Translations into English; Pakistan -- Social life and customs -- Fiction; India -- History -- Partition, 1947 -- Fiction; India -- Social life and customs -- Fiction